Morphogenesis of sens the brown-marbled grouper Epinephelus fuscoguttatus (Forsskål) - Mukai, Yukinori; Lim, Leong-Seng (Taylor & Francis, 2014)
The morphogenesis of sense organs and related behavioural changes in the hatchery-reared brown-marbled grouper Epinephelus fuscoguttatus larvae were examined to gain better understanding of its early life history because ecological field observations for grouper species is difficult. The newly hatched larvae (2.1 mm total length) had developing eyes and otic vesicles, a pair of free neuromast on the head and ciliated olfactory epithelium. At 3 days post hatching (dph), the eyes became fully pigmented with pure-cone retinae, the semicircular canals formed in the inner ear, and the larvae (2.8 mm) were able to swim horizontally, preying on rotifers. Retinal rods and the intra-oral taste buds at pharyngeal appeared next. The olfactory lamellae and the head lateral line system then formed, and the inner ears developed completely in the larvae during the metamorphosis period (15–40 dph; 5.1–18.1 mm). At settlement (50 dph; 32.8 mm), the fish possessed taste buds in the mouth entrance region, and the lateral line system developed completely. The sensory development correlates well with the known aspects of its life history at sea whereby the larvae can feed early and avoid predators during the passive drift, are able to swim shoreward to search nursery ground along the metamorphosis stage and survive in seagrass beds at settlement.